Development of Wheat (Triticum aestivum L.) Populations for Drought Tolerance and Improved Biomass Allocation Through Ethyl Methanesulphonate Mutagenesis - OlaOlorun, Boluwatife M.; Shimelis, Hussein; Laing, Mark; Mathew, Isack (Frontiers in Agronomy, 2021)
The narrow genetic variation for drought adaptive traits and biomass allocation in wheat (Triticum aestivum L.) presents a major bottleneck for breeding. Induced mutagenesis creates genetic variation and complements conventional breeding for drought tolerance improvement. The aims of this study were to induce mutations in wheat genotype LM43 using three ethyl methanesulphonate (EMS) treatments, and to develop mutant populations for improving drought tolerance, biomass allocation and agronomic performance. Experiments were conducted under controlled and field conditions at the University of KwaZulu-Natal. Data on percentage germination (%G), days to 90% maturity (DTM), plant height (PH), shoot biomass (SB), root biomass (RB), root-shoot ratio (RSR), spike length (SL), spikelet count (SPS), thousand seed weight (TSW), and grain yield (GY) were collected from M1 to M4 generations. Significant (p < 0.001) differences among individuals and generations were observed for all the assessed traits and the generation × population interaction effects were significant (p < 0.01) for SB, TSW, and GY due to EMS treatments. The differences among the generations showed that the mutagenic effects were cumulative and exhibited clear segregations in subsequent generations. The new selections with unique biomass allocation, drought response and agronomic performance will be useful for wheat improvement programs.